Conceptual model to predict Filipino teachers' adoption of ICT-based instruction in class: using the UTAUT model. Issue 4 (2nd October 2022) - Kim, Jinhee; Lee, Kate Sang-Soog
ABSTRACT: For scaling up pedagogical innovation with information and communications technology (ICT), governments around the world put a concerted effort into teachers' acceptance of ICTs and the actual use of ICTs for instruction, yet there is limited literature about the conceptual framework of teachers accepting the ICTs and their usage for instruction typically in the Asia-Pacific region. To fill such gaps in the current literature, this study aims to construct a conceptual model of teachers' effective practice of ICT-based instruction under a mandatory context in the Philippines based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Through a survey conducted by 305 secondary school teachers in the Philippines, this study revealed that performance expectancy (PE), effort expectancy (EE), social influence (SI) and education policy (EP) have significant effects on teachers' behavioural intention to use ICTs (BI) and BI, teachers' ICTs use habit (IUH) and facilitating conditions (FCs) have positive effects on the actual use of ICTs for instruction. The study then recommends a series of actions to improve research and policy on teachers' use of ICT-based instruction.